(untitled) - William Bolton (1933- (London, 1991)
The book provides an introduction to the principles of industrial control and instrumentation. It gives an introduction to the basic concepts and terminology of measurement and control systems; offers more detailed discussions of the elements used to build up such systems; brings the elements together in a consideration of measurement and control systems
Keywords: industries - process control - instrumentation